2016
DOI: 10.3892/ijo.2016.3361
|View full text |Cite
|
Sign up to set email alerts
|

Regorafenib as a potential adjuvant chemotherapy agent in disseminated small colon cancer: Drug selection outcome of a novel screening system using nanoimprinting 3-dimensional culture with HCT116-RFP cells

Abstract: Colon cancer is one of the leading causes of cancer death worldwide. Adjuvant chemotherapy following primary surgical treatment is suggested to be beneficial in eradicating invisible disseminated small tumors in colon cancer; however, an effective drug remains to be developed. Recently, we reported a novel drug screening system using a nanoimprinting 3-dimensional (3D) culture that creates multicellular spheroids, which simulate in vivo conditions and, thereby, predict effective drugs in vivo. This study aimed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 32 publications
1
8
0
Order By: Relevance
“…Moreover, daily regorafenib administration at 30 mg/kg suppressed tumor growth in a highly aggressive murine CT26 metastatic colon cancer model 55 . Although similar results were observed in different HCT116-bearing mouse models 53,56 , it has been noted that a lower regorafenib dose, such as 10 mg/kg/day, can delay tumor growth 47 , even in oxaliplatin-refractory CRC-PDX 50 .…”
Section: Regorafenib and Crcsupporting
confidence: 73%
See 1 more Smart Citation
“…Moreover, daily regorafenib administration at 30 mg/kg suppressed tumor growth in a highly aggressive murine CT26 metastatic colon cancer model 55 . Although similar results were observed in different HCT116-bearing mouse models 53,56 , it has been noted that a lower regorafenib dose, such as 10 mg/kg/day, can delay tumor growth 47 , even in oxaliplatin-refractory CRC-PDX 50 .…”
Section: Regorafenib and Crcsupporting
confidence: 73%
“…A study performed with the human CRC cell lines HCT15, DLD-1, HT29, and HCT116 showed a drastic decrease in cell viability when regorafenib was administered at doses higher than 5 µM 47 , an effect that was also observed in SW480 48 , KM12SM, Caco-2, LoVo, WiDr, and RKO CRC cells 49 . Cell proliferation inhibition was also corroborated in a panel of in vitro models 5052 , as well as in an HCT116 nanoimprinting 3D culture 53 and in cell lines established from CRC primary tumors 54 . Moreover, daily regorafenib administration at 30 mg/kg suppressed tumor growth in a highly aggressive murine CT26 metastatic colon cancer model 55 .…”
Section: Regorafenib and Crcmentioning
confidence: 71%
“…Human colon cancer HCT116 cells (CCL-247; American Type Cell Collection) stably expressing RFP (HCT116-RFP), established in our previous study [ 48 ], were used. Human gastric cancer NUGC4-RFP cells (Anticancer) were also used in this study.…”
Section: Methodsmentioning
confidence: 99%
“…Using polymeric microparticle surfaces to create 3D tumors, they found that 2D MCF7 cells were significantly more sensitive to these drugs than 3D MCF7 cells, with a 12-to 23-fold disparity in the IC50 values. The study also showed that the sum of collagen in the 3D model was 2 times greater than that of 2D condition and the expression of many genes were different, possibly accounting for the difference in responses to the drugs (Horning et al, 2008 Based on their 3D culture studies, the authors were able to demonstrate effective and non-effective drugs for colon cancer treatment (Yoshii et al, 2016). …”
Section: Applications In Anticancer Drug Screeningmentioning
confidence: 99%